Sirtuin 1 serum concentration in healthy children - dependence on sex, age, stage of puberty, body weight and diet - Fedorczak, Anna; Lewiński, Andrzej; Stawerska, Renata (Frontiers in Endocrinology, 2024)
Sirtuin 1 (SIRT1) is known to be involved in sensing cellular energy levels and regulating energy metabolism. Studying SIRT1 in the context of children's health may have implications for understanding growth processes and development of puberty, metabolic disorders and age-related dis-eases in early life. The aim of this study was to evaluate fasting serum SIRT1 levels in healthy children, and to analyse the influence of age, sex, puberty, body weight, height, and diet on its concentration. 47 healthy children aged 4-14 with weight and height within normal range and no chronic disease were included into the study. Fasting serum SIRT1 concentrations were estimated by Enzyme Linked Immunosorbent Assay (ELISA). Results showed that serum SIRT1 concentrations in healthy children did not differ with respect to sex, age, height, weight and puberty. Whereas, it appeared that higher frequency of fruits, vegetables and dairy products consumption was associated with an increase in serum sirtuin 1 levels.